The Impact of TWICE as Brand Ambassadors that Increase Consumers’ Purchasing Decision on Indonesian Local Skincare with Brand Image as the Mediator: in the Case of Scarlett Whitening - Felicia Angeline Nurcahya; Belinda Gunawan (iBuss Management, 2023)
Theoretically, brand ambassadors are a media used by businesses to engage with and connect with the public to promote sales. Hence, this study is being conducted to evaluate and identify the effects of TWICE as the brand ambassador towards consumers’ purchasing decision of Scarlett Whitening with brand image as the mediator. In this study the researchers used the framework made by Greenwood (2012). The researchers decided to employ unconstrained or simple random sampling as the sample design and has obtained valid respondents as many as 90 responses to be analyzed further in this study. The data of this study will be analyzed using the WARPPLS 8.0 software and the PLS-SEM technique. The results of this study showed that brand ambassadors had a direct influence on consumers’ purchasing decision as well as the brand image. Moreover, it is proven that brand image can mediate brand ambassadors towards consumers’ purchasing decision. This research is limited to the research scope which only examined two variables toward a specific industry. Therefore, suggestions for future research have been included in this study.Keywords: brand ambassador, brand image, consumers’ purchasing decision.